(untitled) (Medical Forum Monthly, 2023)
Objective: To determine the role of remdesivir administered for treatment of hospitalized coronavirus disease 2019 (COVID-19) in terms of rapid clinical improvements. Study Design: Retrospective comparative study Place and Duration of Study: This study was conducted at the Department of Pulmonology and Covid-19 department, Recep Tayyip Erdogan Hospital Muzaffargarh from April 2020 to December 2021. Materials and Methods: A total of 923 patients were enrolled in study. Clinical outcomes like hospital stay, ICU stay, mechanical ventilation time, discharge from hospital and duration of death after admission and mortality rate of patients treated with remdesivir and who were treated without remdesivir was taken from hospital record. Data was analyzed by using SPSS version 24. Results: The mean length of stay of remdesivir patients was 8.19±5.71 days with 95% C.I (7.68-8.70) and non-remdesivir patients was 6.07±5.66 days with 95% C.I (5.54-6.60), and the difference was statistically significant, (p=0.000). The most common diagnosed complication in remdesivir patients was diabetes mellitus 7.6% and the second most common complication was sepsis 6.0%. Among total 14.8% of remdesivir patients needed to admit in ICU versus 14.9% with (p=0.980). Distribution of mortality was 39.5% of remdesivir patients versus non-remdesivir 26.3%. Conclusion: Remdesivir is associated with poor clinical outcomes, mean hospital stay, ICU stay and death rate is higher in patients treated with remdesivir, as compared to those treated without remdesivir. Final outcome regarding discharge of patients is also better in without remdesivir group.